Analysis Of The Effect Of Financial Ratios On Financial Performance In Food And Baverage Companies Listed On The Indonesian Stock Exchange In 2017-2021 - Rina Rohmantiana; Moechammad Nasir (IAIN Palopo, 2023)
Food and Baverage companies are one of the manufacturing industry companies, which have a role in economic growth in Indonesia. The purpose of this study was to analyse the effect of financial ratios on financial performance in food and baverage companies listed on the Indonesian stock exchange in 2017-2021. this research uses quantitative descriptive research, sampling technique with purposive sampling. liquidity ratio has a negative and insignificant effect on financial performance. Profitability ratio has a negative and insignificant effect on financial performance. Solvency ratio has a positive and insignificant effect on financial performance. Activity ratio has a negative and insignificant effect on financial performance. Liquidity, profitability, solvency and activity ratios together have a positive and significant effect on financial performance.